Afecto y memoria: el efecto de la publicidad emocional sobre la recordación de marca (Tema Central) - Benavides Polo, Claudia (2025)
The effect of emotions on memory has been considered in research from psychology and neuroscience, and has been extended to multiple knowledge areas, including marketing and advertising. Studies have proven that advertisements that include emotional content have a positive influence on advertisement recall. This study extends these theories by exploring how emotional advertising affects brand recall, a crucial indicator in marketing. An experiment with 38 participants was conducted to investigate whether this relationship is applicable in the Latin American context and if emotional advertising enhances the recall of brand components typically necessary for post-advertisement decision-making. An experimental design of only posttest was carried out. The quantitative measures were taken through surveys and processed through t student tests and correlation quotients. The given results revealed that advertisements with an emotional approach in magazines led to higher brand recall measures compared to rational advertisements. This experimental study, supported by prior research, suggests that eliciting emotions in individuals can enhance ad effectiveness.